The University of the West Indies Distance Teaching Project: Report to the Advisory Council - Lalor, Gerald C. (UWI, 1983)
This report is concerned with the development and activities of the University of the West Indies Distance Teaching Project (UWIDITE), through which the university conducted experiments on the use of telecommunications to extend its regional services. Preliminary studies led to recommendations for a small system to be used for inservice teacher education for examinations, agricultural extension and health training. The report lists UWIDITE programme development services and provides guidelines for the preparation of student materials for distance teaching programmes. These guidelines suggest inclusion of a general introduction as well as a course introduction, and describe course development techniques. The final section of the report is a synopsis of strategies to make effective use of interactive audio through humanizing the experience, grouping the participants, preparing course materials, encouraging discussion and making listening easier
Keywords: UWIDITE